2023
DOI: 10.1136/bmjopen-2023-073777
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic impact of adverse drug reactions in hospitalised patients: prospective matched nested case–control study in Ethiopia

Abstract: ObjectivesThe purpose of this study was to assess the clinical and economic impact of adverse drug reactions (ADRs) among patients admitted to the University of Gondar Comprehensive Specialized Hospital (UoGCSH).Design and settingA prospective nested case–control study was conducted at the UoGCSH among admitted adult patients with (cases) and without ADRs (controls) between May and October 2022.ParticipantsAll eligible adult patients admitted in the medical ward of the UoGCSH during the study period were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Of 78 studies, 27 studies [ 18 44 ] were carried out among general patients, while the remaining studies [ 45 95 ] were carried out among specific patients. Seventeen studies [ 18 22 , 24 , 26 , 31 , 33 35 , 38 , 39 , 41 – 43 , 51 ] reported the prevalence of ADEs leading to hospital admissions, while 30 studies [ 18 , 19 , 22 33 , 35 , 37 41 , 43 , 44 , 65 , 80 , 85 88 , 91 , 95 ] reported the prevalence of ADEs during hospitalization. Twelve studies [ 18 , 19 , 22 , 24 , 26 , 31 , 33 , 35 , 38 , 39 , 41 , 43 ] reported ADE occurrence in both settings.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 78 studies, 27 studies [ 18 44 ] were carried out among general patients, while the remaining studies [ 45 95 ] were carried out among specific patients. Seventeen studies [ 18 22 , 24 , 26 , 31 , 33 35 , 38 , 39 , 41 – 43 , 51 ] reported the prevalence of ADEs leading to hospital admissions, while 30 studies [ 18 , 19 , 22 33 , 35 , 37 41 , 43 , 44 , 65 , 80 , 85 88 , 91 , 95 ] reported the prevalence of ADEs during hospitalization. Twelve studies [ 18 , 19 , 22 , 24 , 26 , 31 , 33 , 35 , 38 , 39 , 41 , 43 ] reported ADE occurrence in both settings.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies [ 18 22 , 24 , 26 , 31 , 33 35 , 38 , 39 , 41 – 43 , 51 ] reported the prevalence of ADEs leading to hospital admissions, while 30 studies [ 18 , 19 , 22 33 , 35 , 37 41 , 43 , 44 , 65 , 80 , 85 88 , 91 , 95 ] reported the prevalence of ADEs during hospitalization. Twelve studies [ 18 , 19 , 22 , 24 , 26 , 31 , 33 , 35 , 38 , 39 , 41 , 43 ] reported ADE occurrence in both settings. In addition, 38 studies [ 45 50 , 52 , 54 64 , 66 74 , 76 , 78 , 79 , 82 84 , 89 , 90 , 92 94 ] reported the occurrence of ADEs in the outpatient setting, and four studies [ 53 , 75 , 77 , 81 ] reported ADEs in the community setting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations